Pengaruh Tekanan Karyawan, Tekanan Pemegang Saham dan Gender Diversity terhadap Kualitas Sustainability Report - Nabilah Aisha Putri; Erinos NR (Universitas Negeri Padang, 2023)
The purpose of this research is to examine the impact of employee pressure, shareholder pressure and gender diversity on the quality of sustainability report. To assess the quality of sustainability reports, this study employs the SRQ value, which is a disclosure index based on the GRI-Standard. The population of this research are companies listed on the Indonesia Stock Exchange (IDX) over a five-year period from 2017 – 2021. By using the purposive sampling method, this research obtained 48 samples that met the criteria. This research uses multiple linear regression analysis in hypotheses testing. The findings indicate that employee pressure and shareholder pressure has a negative and significant effect on the quality of sustainability reports. On the other hand, gender diversity do not have any effect on the quality of sustainability reports.Thus, all the hypotheses proposed in this study were rejected.